A Comparative Analysis of the Effectiveness of Four Supply Chain Initiatives to Reduce Deforestation. (June 2015) - Meijer, Karen S.
Deforestation and forest degradation account for around 12–15% of global greenhouse gas emissions and are largely driven by agricultural expansion. In the absence of formal regulation, voluntary initiatives have been established to meet demands from consumers and environmental NGOs. This paper examines what explains the effectiveness of supply chain initiatives to reduce deforestation, comparing four supply chain initiatives in two countries: the Roundtable on Sustainable Palm Oil in Indonesia and the Roundtable on Responsible Soy, the Soy Moratorium and the Cattle Agreement in Brazil. The first two are certification schemes, incentivizing more sustainable production, while the latter two are moratoria under which certain actors no longer purchased from companies that engaged in deforestation after a certain date. The moratoria benefitted from a concentration of power among actors risking loss of customers and able to demand changes in behavior from their suppliers. Certification schemes of multi-stakeholder initiatives are based on consensus and have lower requirements for reducing deforestation. For all initiatives a risk of leakage – deforestation by others, for other purposes, or elsewhere – remains. Little seems to be known regarding the possibilities farmers have to alter production practices, potentially hampering the development of public policies to complement the private initiatives.